Research paradigms in international human resource management: An epistemological systematisation of the field. (May 2020) - Bonache, Jaime; Festing, Marion
The explicit consideration of Research Paradigms in International Human Resource Management, the title of this Special Issue, helps us in analysing and systematising the field to show how research in international human resource management is typically conducted, what preferred perspectives prevail and which approaches have been rather neglected so far. In this introduction, we map the field, and after defining the contours of international human resource management, we use the distinction between positivism and interpretivism to outline implications for the goals of international human resource management studies and associated ontological and epistemological assumptions. Next, we analyse research methods, ways to construct research questions, researchers' roles, sampling procedures, data collection techniques, key theoretical contributions, focus on context in theory construction, quality indicators of data analysis and evaluation criteria in each of the two key research paradigms when studying international human resource management issues. In so doing, we offer a framework for the contributions made to this Special Issue, including literature reviews focusing on the systematisation of international human resource management research, using various paradigm lenses and specific methods. We sincerely hope that the notions, typologies and contributions included in this Special Issue, all based on extensive literature reviews, will help advance research in international human resource management.